A Minimal Model Shows that a Positive Feedback Loop Between sNHE and SLO3 can Control Mouse Sperm Capacitation - de Prelle, Bertrand; Lybaert, Pascale; Gall, David (Frontiers in Cell and Developmental Biology, 2022)
When mammalian spermatozoa are released in the female reproductive tract, they are incapable of fertilizing the oocyte. They need a prolonged exposure to the alkaline medium of the female genital tract before their flagellum gets hyperactivated and the acrosome reaction can take place, allowing the sperm to interact with the oocyte. Ionic fluxes across the sperm membrane are involved in two essential aspects of capacitation: the increase in intracellular pH and the membrane hyperpolarization. In particular, it has been shown that the SLO3 potassium channel and the sNHE sodium-proton exchanger, two sperm-specific transmembrane proteins, are necessary for the capacitation process to occur. As the SLO3 channel is activated by an increase in intracellular pH and sNHE is activated by hyperpolarization, they act together as a positive feedback system. Mathematical modeling provides a unique tool to capture the essence of a molecular mechanism and can be used to derive insight from the existing data. We have therefore developed a theoretical model formalizing the positive feedback loop between SLO3 and sHNE in mouse epididymal sperm to see if this non-linear interaction can provide the core mechanism explaining the existence of uncapacited and capacitated states. We show that the proposed model can fully explain the switch between the uncapacitated and capacited states and also predicts the existence of a bistable behaviour. Furthermore, our model indicates that SLO3 inhibition, above a certain threshold, is effective to completely abolish capacitation.